2011
DOI: 10.1590/s0104-11692011000600012
|View full text |Cite
|
Sign up to set email alerts
|

Risk of surgical site infection in patients undergoing orthopedic surgery

Abstract: 4This study aimed to identify risk factors associated with surgical site infections in orthopedic surgical patients at a public hospital in Minas Gerais, Brazil, between 2005 and2007. A historical cohort of 3,543 patients submitted to orthopedic surgical procedures. A descriptive analysis was conducted and surgical site infection incidence rates were estimated. To verify the association between infection and risk factors, the Chi-square Test was used. The strength of association of the event with the independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
4
17

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 12 publications
2
44
4
17
Order By: Relevance
“…The prevalence of SSI in the current study is higher than that reported by other authors 2,3,4,6,7,8,9,10 . However, similar prevalence of SSI was observed in other studies done by 1,12, .…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…The prevalence of SSI in the current study is higher than that reported by other authors 2,3,4,6,7,8,9,10 . However, similar prevalence of SSI was observed in other studies done by 1,12, .…”
Section: Discussioncontrasting
confidence: 85%
“…The likely explanation for these observations may be increased preoperative hospital stay period predisposes to skin colonization by hospital microbes that are resistant to antibiotics and so it is important to minimize preoperative hospitalization period in order to lower SSI rate 2,8,11 . However (8) found preoperative length of hospitalization not to have any association with development of SSI. This difference might be reflecting low rate of hospital acquired cross infection or absence of overcrowding there setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentre estas repercussões, aquela que acomete mais diretamente a estrutura hospitalar é representada pelo aumento da estadia e, consequentemente, dos custos associados a esta; isto é, o tratamento de um paciente com infecção triplica em relação a um paciente que não a desenvolve [1][2][3] . A contaminação ambiental é um dos fatores extrínsecos que influenciam diretamente a ocorrência de ISC; por isso, a prevenção da contaminação ambiental seria uma das formas de prevenção de sua ocorrência 3 .…”
Section: Introductionunclassified
“…1,2 Deep seated bacterial infection after hip and knee replacement are recognized as a serious threat to patients. 3 Fungal infections, such as candidemia are also associated with economic burden caused by increased length of hospital stay (average of approximately 11 days more per case) and threefold increased mortality rate.…”
Section: Introductionmentioning
confidence: 99%